Communication skill and mathematics conceptual understanding of senior high school students. (November 2019) - Mulbar, U; Assagaf, S F; Arfah, A.
Abstract: The aims of this research are to describe about mathematical communication ability either written or oral form and find the relation between mathematical communication and mathematics conceptual understanding of senior high school students. Mathematical communication is process of social interaction involve process of exchange and reflection of information, ideas, and understanding the mathematics from someone to others. Conceptual understanding of mathematics involve understanding of the basic concepts behind algorithms in mathematics. This study used mixed method, quantitative and qualitative method. Mathematical communication ability is measured by written test, and non-test with specific indicators to measure mathematical communication. In other hand, mathematics conceptual understanding is measured by written test. The number of subject in qualitative phase is four subjects categorized based on their mathematical communication ability, namely very low (VL), low (L), high (H), and very high (VH). The result of this research revealed the students in doing mathematical communication of every ability level. In addition, we find that there is no relation between mathematical communication and mathematics conceptual understanding of students.